The latest method, home instruction by mail, dancing courses ... - Frank, Charles J. (Charles Julius) (Philadelphia, Pa., The Beacon Academy, 1922)
This is a series of three pamphlets, each from sixteen to twenty-four pages, that describes the waltz, the foxtrot, and the one step. Designed for those who "know nothing at all about Modern Dances," each pamphlet provides preliminary exercises and basic lessons for execution of the steps.
v. 1. The waltz.--v. 2. The fox trot.--v. 3. The one step.
LC has v. 1-3 only.
Available also through the Library of Congress Web site as facsimile page images.
Keywords: Waltz -- Handbooks, manuals, etc; Foxtrot (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals